Talleres de psicomotricidad en aulas de inclusión, en un preescolar enriquecido por la diversidad: fundación centro San Juan de Jerusalén, Quito – Ecuador - Sigüenza Hinostroza, Sonia Raquel (2016)
Then, we have the application of psychomotricity workshops whose population is made up of children with cerebral palsy and their regular children, all belonging to the preschool of the Fundación Centro San Juan de Jerusalén, pioneer institution in inclusive education for 25 years in Quito - Ecuador, psychotherapeutic, structuring, safe and container work where children will experience motor, sensory, body, playful and emotional experiences that will allow them to involve and reinvolve their body within their psychic and physical dimension, taking into account the presence of others, the way these workshops contribute to the process of learning and social adaptation, the construction of autonomy and the group consolidation of children with disabilities and without it, twinned by their desire to grow and share.